Experimental and numerical studies of porous media combustion in micro burner - Ahmed Janvekar, Ayub; Abdullah, Mohd Zulkifly; Ahmad, Zainal Arifin; Abas, Aizat; Zuber, Mohammad; Ismail, Ahmad Kamal; Hussien, Ahmed; Kataraki, Pramod; Mohamed, Mazlan; Bashir, Musavir; Husin, Azmi; Fadzli, Khairil (Penerbit Akademia Baru, 2018)
Porous media combustion has been key point of interest for researchers from past couple of decades due its numerous advantages, such as remarkable low emission levels without compromising thermal efficiency. In this present work, dual layered micro burner was built with predefined thickness of reaction and preheat layer. Reaction layer was made up of alumina (discrete type) while preheat layer porcelain (foam type) material. Burner was successfully built to undergo both surface and submerged flames. A concept of equivalences ratio was enabled since its premixed combustion with natural air as one of the inlet along with butane. Trials were not just restricted at stoichiometric ratio but also carried out up to ultra-lean region. Additionally, numerical simulation was performed using commercially available computational fluid dynamics package so that porous media combustion phenomenon can be better analyzed and predicted. Finally, Thermal efficiency was calculated at critical equivalence ratios and emission parameters such as NOx and CO was continuously monitored which were under controlled limits.